Komposisi Kimia Cacing Kacang (Sipunculus nudus) di Kabupaten Raja Ampat dan Kabupaten Manokwari - Juliana Leiwakabessy; Rico R.R Mailissa; Simon P.O Leatemia (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2017)
Phylum Sipuncula is an unique marine creature, as its external morphology. This animal like a worm, and thus its name peanut worm. Papua people live in coast nearby ate this organism as food, but its nutrition status was not yet discussed. Research was done in March-Paril 2014, with the goal of determining chemical composition of S. nudus taken from Raja Ampat and Manokwari. Results showed that water content S. nudus of Sowi 4 Manokwari) was 8.06%, highest fat content found on sample of Kampung Amdui Raja Ampat (1.70%), as well as protein ( 82.46%). The highest carbohydrate was in sample of Sowi 4 Manokwari (7.26%), but the fibre was in sample of Kampung Amdui Raja Ampat(11.07 Mg/100g) and 297.01Mg/100g. Other mineral such as kalium od Sowi 4 Manokwari sample was 207.48Mg/100g. The difference on size length and weight were not affect the percentage of nutrition value of S. nudus.